The Engagement of Public Participation in Participatory Art Practices - Wan Jamarul Imran, Wan Abdullah Thani; Mohamad Faizuan, Mat (UNIMAS Publisher, 2024)
Participatory art practices promote public involvement or participation as part of the entity that will assist the artist to create the artwork. The participative type approach seems challenging the usual practices of the artist, even the artistic outcomes or artform or artwork will be in different contexts. The study was to identify a gap remains in understanding the influence and purpose from the participant that can lead to their participation. It was focusing on the participants’ perception as a co-creator in participatory art practices. Data was gathered from questionnaires posed to respondents who participated in the conducted participatory art project. The thematic analysis was used to identify the participant purpose of involvement in participatory art. Result found that the participation from the public was based on self-inclination and their engagement in the activity contribute significantly to the socially engaged context. Public engagement in participatory art has encouraged the happening of a constructive relationship between the artist and the proposed concept.